A New Era of Catalysis: Efficiency, Value, and Sustainability. Issue 6 (June 2014) - Cheng, Soofin; Lin, Shawn D.
<x xml:space="preserve">Abstract</x> Value proposition: Global warming and climate change urge the chemical industry to develop new processes, in which sustainability is a necessity and requirement. Catalysis is recognized to be one of the key technologies in enabling sustainability. This special issue, assembled by guest editors Soofing Chen and Shawn D. Lin, highlights some of the best work presented at "The 6th Asia–Pacific Congress on Catalysis (APCAT‐6)", with as major theme "New Era of Catalysis: Efficiency, Value, and Sustainability".<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>